A Guarantee – Does the Obligee Agree? A Risk Premium Decomposition of Sub-Sovereign Bond Spreads - David Knezevic; Niclas A. Krüger; Martin Nordström (Örebro University School of Business, 2019)
The purpose of this paper is to investigate if credit markets believe in the existence of a central government guarantee and if this can be observed in the yield spread of the municipal sector. This is done by decomposing the municipal bond yield spread into liquidity and credit risk premiums by variance decomposition in a vector autoregressive setting – an approach which, to our knowledge, has not been previously suggested. Our results show that 62% or 50 basis points of the yield spread is explained by the chosen liquidity and credit variables. The liquidity risk premium makes up 35% or 28 basis points of the yield spread and credit makes up 27% or 22 basis points. Thus, investors and creditors in general do not believe in the existence of such a guarantee.
Keywords: G12; G23; H74; 330; Municipality bonds; risk premium; credit risk; liquidity risk; yield spread